Constraints upon fault zone properties by combined structural analysis of virtual outcrop models and discrete fracture network modelling. (November 2021) - Ceccato, Alberto; Viola, Giulio; Antonellini, Marco; Tartaglia, Giulia; Ryan, Eric J.
Abstract: The permeability structure of a fault zone is strongly dependent on the occurrence of meso-scale fracture patterns within the damage zone. Here, structural analyses of Virtual Outcrop Models (VOM) integrated with Discrete Fracture Network (DFN) modelling are used to constrain the relationship between meso-scale fracture patterns and the bulk permeability of a regional-scale fault zone. The Goddo Fault Zone (GFZ, Bømlo – Norway) is a long-lived extensional fault zone cutting across a granodioritic body developed during the long-lasting rifting of the North Sea. Fracture geometrical characteristics and the spatial variation of fracture intensity derived from VOM structural analysis were adopted as input for stochastic DFN models representing selected portions of the GFZ to constrain the variability of the structural permeability tensor K related to the mesoscopic fracture pattern. The intensity of fault-related fracture set(s), and the associated structural permeability computed with DFN models, likely exhibits a decreasing power-law trend within the damage zone with increasing distance from the fault cores. The orientation of the maximum K tensor component is controlled by the intersection direction of the dominant fracture sets. These results highlight the fundamental role of mesoscopic fracture patterns in controlling the bulk petrophysical properties of large fault zones. Highlights: Virtual outcrop analysis and modelling constrain meso-scale fault zone permeability. Power-law decreasing trend for fracture intensity in (asymmetric) damage zone. Permeability tensor magnitude is linearly proportional to total fracture intensity. Largest permeability observed parallel to dominant fracture sets intersections. Bulk fault zone permeability tensor is strongly oblate.